2007
DOI: 10.1007/s10452-007-9111-5
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical limnology of a wind-swept tropical highland reservoir

Abstract: Valle de Bravo (VB) is a tropical reservoir located (19°21 0 30@ N, 100°11 0 00@ W) in the highlands of Mexico. The reservoir is daily swept by strong (7.4 m s À1 mean speed) diurnal (12:00-19:00 h) winds that blow along its two main arms. As expected from its fetch (6.9 km) and its depth (21.1 m mean), the reservoir behaves as a warm monomictic water body. During 2001, VB was stratified from February to October, and well mixed from November to January. Its mean temperature was 19.9°C; the maximum found was 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
87
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(107 citation statements)
references
References 22 publications
(22 reference statements)
17
87
0
3
Order By: Relevance
“…These changes are typical for warm monomictic water bodies as reported by Hutchinson and Loffler (1956) and by Tundisi (1994), but differ from the warm polymictic thermal cycle reported by Lewis Jr (1983) for other lakes at LG's latitude with similar depths. Nevertheless, the warm monomictic cycle of LG is consistent with the thermal cycle described by Merino-Ibarra et al (2007) for Valle de Bravo reservoir, located at 1780 m a.s.l., 106 km SW from LG. Similar thermal and oxygen profiles in the water column were observed by Vazquez et al (2004) in a tropical lake with an average water temperature higher than LG (21 to 26…”
Section: > Lg Thermal Stratification Mixing Regime and Oxygen Distrisupporting
confidence: 86%
See 1 more Smart Citation
“…These changes are typical for warm monomictic water bodies as reported by Hutchinson and Loffler (1956) and by Tundisi (1994), but differ from the warm polymictic thermal cycle reported by Lewis Jr (1983) for other lakes at LG's latitude with similar depths. Nevertheless, the warm monomictic cycle of LG is consistent with the thermal cycle described by Merino-Ibarra et al (2007) for Valle de Bravo reservoir, located at 1780 m a.s.l., 106 km SW from LG. Similar thermal and oxygen profiles in the water column were observed by Vazquez et al (2004) in a tropical lake with an average water temperature higher than LG (21 to 26…”
Section: > Lg Thermal Stratification Mixing Regime and Oxygen Distrisupporting
confidence: 86%
“…Algal blooms occurred frequently over the stratification period and can be seen as an additional eutrophication indicator. The same observations were made at the Valle de Bravo reservoir (Merino-Ibarra et al, 2007), at Lake Lago de Chapala (Lind and Davalos-Lind, 2002), and at Lake Lago de Patzcuaro (Berlanga-Robles et al, 2002), all of which are located in sub-tropical areas of Mexico. This study confirms that cultural eutrophication is a major problem in several Mexican water reservoirs.…”
Section: > Chlorophyll a Secchi Depth Trophic State And Water Qualimentioning
confidence: 58%
“…Furthermore, turbidity usually peaks in the thermocline region, which is closely related to the location of the maximum density gradient, so low turbulence stabilizes the sediments in the vertical water column (Elçi 2008). As a result, the degradation of water quality in the summer resulting from thermal stratification has been observed in many reservoirs and lakes around the world (Elçi 2008;Merino-Ibarra et al 2008;Wilhelm and Adrian 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Since that incident some studies have been carried out on several reservoirs in South and Central America documenting blooms and progenitor species (Díaz-Pardo et al, 1998;Lind and Davalos-Lind, 2002;Ramirez et al, 2002;Bittencourt-Oliveira et al, 2005;Frias et al, 2006;Merino-Ibarra et al, 2007;Berry and Lind, 2010;Vasconcelos et al, 2010;Rejmánková et al, 2011). A review by Dorr et al (2010) revealed that there has been increased cyanobacterial bloom occurrence in water bodies in South America requiring better methods for screening and testing of cyanobacterial toxins.…”
Section: Introductionmentioning
confidence: 99%